2014
DOI: 10.1111/cpr.12094
|View full text |Cite
|
Sign up to set email alerts
|

IKVAV regulates ERK1/2 and Akt signalling pathways in BMMSC population growth and proliferation

Abstract: ObjectivesThe molecular mechanism of bone marrow mesenchymal stem cell (BMMSC) population growth and proliferation, induced by Isoleucyl-lysyl-valyl-alanyl-valine (IKVAV), was explored in this study.Materials and methodsIKVAV peptides were synthesized by the solid-phase method. Influence of IKVAV on BMMSC population growth and proliferation were investigated by assays of CCK-8, flow cytometry, real-time PCR and western blotting.ResultsIKVAV peptide was found to induce proliferation and proliferating cell nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 82 publications
(98 reference statements)
0
31
0
Order By: Relevance
“…Ile‐Lys‐Val‐ala‐Val directly participates in signaling pathways and enhances bone marrow mesenchymal stem cell (BMMSC) proliferation. The IKVAV peptide directly attaches to the cell membrane and activates the mitogen‐activated protein kinase/extracellular signal‐regulated kinase and phosphatidylinositol 3‐kinase/protein kinase B (PI3K/Akt) signaling pathways . The IKVAV epitope is mediated through the β1 integrin receptor, and with the increase in β1 integrin signaling, it suppress astroglysis in ependymal cells .…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ile‐Lys‐Val‐ala‐Val directly participates in signaling pathways and enhances bone marrow mesenchymal stem cell (BMMSC) proliferation. The IKVAV peptide directly attaches to the cell membrane and activates the mitogen‐activated protein kinase/extracellular signal‐regulated kinase and phosphatidylinositol 3‐kinase/protein kinase B (PI3K/Akt) signaling pathways . The IKVAV epitope is mediated through the β1 integrin receptor, and with the increase in β1 integrin signaling, it suppress astroglysis in ependymal cells .…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…The IKVAV peptide directly attaches to the cell membrane and activates the mitogen-activated protein kinase/extracellular signalregulated kinase and phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathways. 16 The IKVAV epitope is mediated through the β1 integrin receptor, 17 and with the increase in β1 integrin signaling, it suppress astroglysis in ependymal cells. 18 Dorsal root ganglion (DRG) cells were directed along a path of bound IKVAV peptide onto the middle of a gradient of the peptide.…”
Section: D Environmentmentioning
confidence: 99%
“…Extracellular signal-regulated kinases (ERK1/2) and PI3K-Akt signalling pathways have been reported to play an important role in cell proliferation. 25,49 Western blot was performed to monitor the key proteins of the ERK1/2 and PI3K-Akt signalling pathways. It was found that significant phosphorylation of ERK1/2 and Akt was rapidly induced by LIPUS ( Figure 6A…”
Section: Activation Of Erk1/2 and Akt In Lipus-induced Had-mscsmentioning
confidence: 99%
“…Phosphorylated Akt acts on the downstream target factors and plays a role in cell cycle regulation and cell growth. It has been reported that PI3K‐Akt pathway serves an important role in the proliferation of MSCs . However, whether ERK1/2 and PI3K/Akt signalling pathways are involved in the effect of LIPUS on proliferation of hAD‐MSCs are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The new regenerated nerves on 7 and 35 days postimplantation were collected for RNA expression analysis followed by our previous work [23]. Briefly, total RNA was isolated using Trizol reagent (Invitrogen, Carlsbad, USA) and was reverse transcribed into cDNA.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%